Frontline Science: TLR3 activation inhibits food allergy in mice by inducing IFN-γ+ Foxp3+ regulatory T cells. Issue 6 (18th April 2019) - Hong, Jing-Yi; Li, Shan-Shan; Hu, Tian-Yong; Liu, Zhi-Qiang; Yu, Dian; Yu, Hai-Qiong; Guan, Li; Wu, Gao-Hui; Zeng, Hao-Tao; Liu, Zhi-Gang; Yang, Ping-Chang
Abstract: The pathologic feature of food allergy (FA) is the aberrant Th2-biased immune response in the intestine. Regulatory T cells (Tregs) play an important role in the suppression of aberrant immune response. The activities of the TLRs regulate multiple cell functions. This study aims to investigate the role of TLR3 activation in the regulation of Th2-biased immune response in the intestine by the generation of inducible Tregs (iTregs). In this study, polyinosinic polycytidylic acid (polyI:C) was used as an activator of TLR3. An FA mouse model was developed to establish the Th2-biased inflammation in the intestine. The effects of TLR3 activation on the generation of iTreg were tested in the culture and in mice. We observed that exposure to polyI:C induced IFN-γ + Foxp3 + iTregs in mouse intestine and in the culture. The IFN-γ + Foxp3 + iTregs showed immune suppressive functions. Exposure to polyI:C increased T-bet levels in CD4 + T cells. The T-bet formed a complex with GATA3 to dissociate Foxp3 from GATA3/Foxp3 complex in CD4 + T cells. The Foxp3 thus gained the opportunity to move to TGF-β promoter to generate iTregs. Administration with polyI:C prevented the development of FA and inhibited existing FA. In conclusion, activation of TLR3 induces IFN-γ + Foxp3 + Tregs, which can prevent FA development and inhibit existing FA in mice. Graphical Abstract: Upon exposure to polyI:C, naïve CD4 + T cells differentiate into IFN-γ + Foxp3 + regulatory T cells (Tregs); the latter inhibits experimental food allergy.